2003
DOI: 10.1056/nejmoa023204
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention of Radiocontrast-Agent–Induced Nephropathy by Hemofiltration

Abstract: In patients with chronic renal failure who are undergoing percutaneous coronary interventions, periprocedural hemofiltration given in an ICU setting appears to be effective in preventing the deterioration of renal function due to contrast-agent-induced nephropathy and is associated with improved in-hospital and long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
266
0
17

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(285 citation statements)
references
References 32 publications
2
266
0
17
Order By: Relevance
“…Two studies by Marenzi et al [94,95] investigated the effect of continuous venovenous hemofiltration in prevention of CIN in patients with severe chronic renal insufficiency (serum creeatinine >2 mg/dL) in comparison with intravenous hydration. Increase of creatinine >25% (5% vs. 50%, respectively; P < 0.001) and inhospital mortality (2% vs. 14%, respectively; P ¼ 0.02) were significantly lower in group with hemofiltration.…”
Section: Hemodialysis and Hemofiltrationmentioning
confidence: 99%
“…Two studies by Marenzi et al [94,95] investigated the effect of continuous venovenous hemofiltration in prevention of CIN in patients with severe chronic renal insufficiency (serum creeatinine >2 mg/dL) in comparison with intravenous hydration. Increase of creatinine >25% (5% vs. 50%, respectively; P < 0.001) and inhospital mortality (2% vs. 14%, respectively; P ¼ 0.02) were significantly lower in group with hemofiltration.…”
Section: Hemodialysis and Hemofiltrationmentioning
confidence: 99%
“…Intravenous hydration with 0.9% SS) 0.9% SS 1 mL/kg/h, 12 hours before and 12 hours after the procedure Several randomized studies and metaanalyses 30,[32][33][34] 0.9% SS is superior to 0.45% SS 23,32 Sodium bicarbonate (154 mEq/L) NaHCO3 3 mL/kg/h, 1 hour before the procedure and 1 mL/kg/h, 6 hours after the procedure Several randomized studies and meta-analyses 32,[49][50][51][52][53][54] Dilute 154 mL of 8.4% sodium bicarbonate in 846 mL of distilled water for obtaining the solution Type of contrast medium Low-osmolality or iso-osmolality contrast medium Some randomized studies and a few meta-analyses [26][27][28] The literature is still controversial whether isoosmolality contrast medium is superior to low-osmolality contrast medium 29 N-acetyl cysteine 600 mg, orally, 12/12 hours, 24 hours before and after the procedure Still controversial 54,55 Large ongoing multicenter study 56 …”
Section: Most Used Methods Evidence Level Commentsmentioning
confidence: 99%
“…46 Prophylactic hemofiltration has been associated with a reduction in the adverse events related to CN in high risk patients. 50,51 On the other hand, early dialysis after contrast medium use showed no benefit regarding the development of CN.…”
Section: Saline Solutionmentioning
confidence: 98%
“…It has been reported that 60-90 % of the contrast medium is removed during 1 session of hemodialysis. Clinical studies have been conducted on the basis of these findings to investigate the efficacy of hemodialysis, hemodiafiltration, and hemofiltration in the prevention of CIN [160][161][162][163][164][165][166][167][168][169]. However, most studies could not demonstrate the efficacy of these procedures in the prevention of CIN.…”
Section: Level Of Evidence: II Grade Of Recommendation: C2 Rationale mentioning
confidence: 99%